(untitled) (Bangladesh Journal of Zoology, 2020)
This study was aimed to identify the present status and threats on the fish diversity of Hatiya Island, Noakhali, Bangladesh. Five sampling stations were at Chairman ghat, Katakhali ghat, Tamruddin ghat, Burirdona ghat, Domar Bazar. Data were collected using questionnaire interviews (QI), focus group discussions (FGD), and key informant interviews (KII). A total of 38 fish species were recorded belonging to 9 orders and 21 families. Siluriformes was the most abundant order (38%), whereas Cyprinidae was the richest family (18.42%). Based on IUCN red list of threatened species 2015, 26% species was categorized as Locally Threatened in Bangladesh, following 13% as Vulnerable, 13% as Endangered, 63% as Least concerned, 3% as Data Deficient (DD) and 8% was Not Threatened (NT). Overexploitation, water pollution, habitat degradation and climate change were identified as the major threats for declining of fish diversity in the study area. This study recommends sustainable fisheries management, restocking economically important fish species, establishment of sanctuary, maintenance of fishing gears, control of pollution, and the implementation of the fish act for conservation of fish biodiversity of the Hatiya Island, Noakhali. Bangladesh J. Zool. 48(1): 45-55, 2020